Komunikasi Politik Anggota DPR RI Dapil Pulau Lombok (Studi Fenomenologi Terpilihnya Fauzan Khalid Pada Pemilu Legislatif 2024) - Hafizni, Moh. (CV. ITTC INDONESIA, 2025)
This study aims to determine the political communication and strategy carried out by Fauzan Khalid in the 2024 legislative general election. Another objective is to determine the implementation of political marketing until he becomes a member of the Indonesian parliament elected for 2024–2029.The study used a phenomenological study with a qualitative approach. The research subjects or informants were Fauzan Khalid's Parliament members, political communication observers in NTB, and several constituents selected based on purposive sampling techniques and collected data through observation (field observation), interviews, and document searches related to Fauzan Khalid's activities and political communication. Data analysis was done by processing, sorting, synthesizing, searching for, finding important data, and deciding what to convey in the research.The study results show that Fauzan Khalid used various effective political communication strategies and marketing methods until he was elected as a member of the Indonesian parliament for this first period. Fauzan also uses multiplatform media and social media as strategies to spread his political messages and ideas to voters.